2020
DOI: 10.1186/s12884-020-2828-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of decision to delivery time interval and its effect on feto-maternal outcomes and associated factors in category-1 emergency caesarean section deliveries: prospective cohort study

Abstract: Background: Category-1 emergency caesarean section delivery is the commonly performed surgical procedure in pregnant women associated with significant mortality and morbidity both in the mother and fetus. The decision to delivery time interval is recommended to be less than 30 min by the Royal College of Obstetricians and Gynecologists as well as the American College of Obstetricians and Gynecologists. This study was designed to evaluate the decision to delivery time interval and its effect on feto-maternal ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
39
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 27 publications
17
39
2
Order By: Relevance
“…In this study, women who were transferred to the operating room before 15 min showed a statistically significant association with recommended DDI than women who were transferred after 15 min. This finding was consistent with study findings in India, Nigeria, Kenya, and Gondar, Ethiopia [ 9 , 10 , 19 , 21 , 22 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, women who were transferred to the operating room before 15 min showed a statistically significant association with recommended DDI than women who were transferred after 15 min. This finding was consistent with study findings in India, Nigeria, Kenya, and Gondar, Ethiopia [ 9 , 10 , 19 , 21 , 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…This study found that 20.3% of EmCS were performed within the recommended time interval of DDI. This is in line with a study conducted in Gondar, Ethiopia, which was 19.3% [ 19 ]. This may be due to the similarity in the accessibility of logistics in hospitals and the practice and experience of professionals.…”
Section: Discussionsupporting
confidence: 92%
“…This outcome was in parallel with a study done at University of Gondar specialized hospital which concluded that 19.6% of clients who undergoes emergency CS were born with the recommended DDI of 30 minutes. 19 But the result was lower than a study conducted in Oman showing that in 23.8% of emergency CS deliveries, a DDI less than 30 minutes was achieved. 20 …”
Section: Discussionmentioning
confidence: 66%
“…Conversely the decision to delivery interval was longer during spinal anesthesia but the low APGAR score and other worse perinatal outcomes were more associated with general anesthesia [ [21] , [22] , [23] ]∗∗,∗∗,∗∗. There is study showing longer time of decision to delivery interval than the recommended time (30 min) for category 1-cesarean section and this was more associated with time taken to collect surgical materials), time spent between decision and arrival to the operation theater and time taken from arrival at the operation theater to the immediate start of skin incision [ 24 ]∗∗. Neonatal morbidity have been compared for general and spinal anesthesia during emergency cesarean section and the General anesthesia was more associated with low 1-min APGAR score, longer time of hospitalization, higher incidence of morbidity, and lower umbilical blood pH [ 25 ]∗.…”
Section: Discussionmentioning
confidence: 99%